Sociodemographic factors related to quality of life among premenopausal women in Ibadan, Nigeria (2015)
Quality of life (QoL) of premenopausal women (PW) was assessed using primary data collected between September and December 2011. A 26-item questionnaire (WHO-QoL BREF) was administered to 285 apparently healthy women selected from two local government areas in Ibadan. The scores were categorized into poor (≤79.53) and good (>79.53) QoL. Multiple logistic regressions were used to study factors associated with QoL. The mean score for the overall QoL (OQoL) was 65.18 ± 11.35 (range = 81.25). The Cronbach’s alpha for all domains as well as the OQoL were within an acceptable range. The proportion of women with good OQoL was significantly higher in the urban areas (18.2 percent) than in the rural areas (9.2 percent) (p < .05). The proportion of respondents with good OQoL was significantly higher for women aged < .01). Teenage participants were almost ten times as likely to have a good social relationship than participants above 35 years of age (odds ratio: 9.52; 95% confidence interval: 1.83–49.40). The authors’ results Received June 29, 2013; revised August 18, 2014; accepted August 28, 2014. Address correspondence to Akinkunmi Paul Okekunle, BSc, MPH, Department of Human Nutrition, Faculty of Public Health, College of Medicine, University of Ibadan, 900001 Ibadan, Oyo State, Nigeria. E-mail: akinokekunle@gmail.com 646 Downloaded by [Texas A & M International University] at 03:05 06 November 2015 Sociodemographic Factors Related to Quality of Life 647 suggest that the WHO-QoL BREF is a reliable instrument for measuring QoL among PW in Nigeria. Younger PW and women in the urban areas were more likely to have good QoL.